State Intervention, Local Indebtedness, Investment Overheating and Their Systemic Background During Global Crisis in China - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
This paper focuses on the immediate economic and systemic reasons of steadily increasing local government indebtedness and investment overheating in China. These two phenomena emerged between 2008 and 2011 as a direct consequence of an external shock caused by the global crisis and the subsequent internal reaction in the form of intensified stimulating state intervention. New chances for resource distribution and investments through state intervention mobilized distribution priorities and politically rational economic behavior of actors, characteristic to party-state systems. Locations of mobilization were defined by the decentralized Chinese system specifics along the intertwined institutional party-state structure. Systemic characteristics and its Chinese specifics together resulted in investment overheating, and steadily growing local indebtedness through large and state-owned enterprises and local governments. This process was further amplified by the characteristics of transforming economy in China as actors in the private sphere were mobilized by the increased input demand of those privileged by the systemic priorities of state intervention.
Keywords: F5; D78; R58; J08; O15; E24; 330; local indebtedness; crisis; party-state systems; resource distribution; state intervention; overheating